Protozoan Parasites and Type I IFNs - Silva-Barrios, Sasha; Stäger, Simona (Frontiers in Immunology, 2017)
For many years, the role of IFN-I has been characterized primarily in the context of viral infections. However, regulatory functions mediated by IFN-I have also been described against bacterial infections and in tumor immunology. Only recently, the interest in understanding the immune functions mediated by IFN-I has dramatically increased in the field of protozoan infections. In this review, we discuss the discrete role of IFN-I in the immune response against major protozoan infections: Plasmodium, Leishmania, Trypanosoma, and Toxoplasma.